Randomized response surface pathway design with skewed starting point and stochastic dose window - Holand, Trond; Evensen, Øystein; Dewi, Sagita; Larsen, Stig (International Journal of Clinical Trials, 2020)
Background: The aim was to introduce response surface pathway (RSP)-design with skewed starting value and stochastic dose-window to estimate optimal efficacy dose (OED) of BP-C2 after IL-1β stimulation in Atlantic salmon. Methods: 54 healthy smolt of Atlantic salmon between 50 and 100 g before habituated to salt water were included. The study was conducted as a one-dimensional, randomized between-patient three-level RSP designed trial with one interventional- and one response variable and odd outcomes. The interventional variable was intraperitoneal injected BPC2 with skewed starting dose of 0.10 mg/100 g related to the initial dose-window <0.02-0.5 mg/100 g. The response variable was the Ct-value of mRNA IL-1β expression 24 hours after injection. Results: Skewed starting value of 0.10 mg/100 g was chosen in the first design-level with a dose-window of <0.0-0.20]. The three smolt obtained a reduction in Ct-value above 15%, and the dose-window adjusted with the lower boundary equals the previous dose. The five smolt at second design-level received 0.16 mg/100g with a dose-window [0.10-0.22]. Four smolt obtained above 15% and one of 0.5% reduction in cycle threshold (Ct)-value. Six smolt in the third design-level received 0.21 mg/100 g and one 0.16 mg/100 g. The mean Ct-value was reduced from 30.0 in the unstimulated situation to 25.0, 24.8 and 26.4 after BP-C2 stimulation of 0.10, 0.16 and 0.21 mg/100 g, respectively. The OED of BP-C2 related to IL-1β was estimated to 0.14 mg/100 g. Conclusions: Skewed starting value in the initial dose-window made the K-adjustment factor and dose-window stochastic. The RSP-procedure works in accordance to the expectation and estimated OED of BP-C2 sufficiently.